Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's solve this problem step-by-step:
### Step 1: Identify the roots of the given quadratic equation
The roots of the given quadratic equation [tex]\(3x^2 + 5x - 1 = 0\)[/tex] are:
[tex]\[ \alpha = -\frac{5}{6} + \frac{\sqrt{37}}{6}, \quad \beta = -\frac{\sqrt{37}}{6} - \frac{5}{6} \][/tex]
### Step 2: Construct equations for the given conditions
#### (a) Equation with roots [tex]\(5\alpha\)[/tex] and [tex]\(5\beta\)[/tex]
To construct the equation with roots [tex]\(5\alpha\)[/tex] and [tex]\(5\beta\)[/tex], we start by substituting [tex]\(x = 5t\)[/tex] into the original equation to form:
[tex]\[ 3\left(\frac{x}{5}\right)^2 + 5\left(\frac{x}{5}\right) - 1 = 0 \][/tex]
Simplifying, we get:
[tex]\[ \frac{3}{25}x^2 + \frac{5}{5}x - 1 = 0 \][/tex]
[tex]\[ \frac{3}{25}x^2 + x - 1 = 0 \][/tex]
Multiplying through by 25 to clear the fraction gives the final equation:
[tex]\[ 3x^2 + 25x - 25 = 0 \][/tex]
#### (b) Equation with roots [tex]\(\alpha^2\)[/tex] and [tex]\(\beta^2\)[/tex]
To construct the equation with roots [tex]\(\alpha^2\)[/tex] and [tex]\(\beta^2\)[/tex]:
[tex]\[ 3(t^{1/2})^2 + 5t^{1/2} - 1 = 0 \][/tex]
Where [tex]\(t = x^2\)[/tex], this simplifies to:
[tex]\[ 3x + 5\sqrt{x} - 1 = 0 \][/tex]
#### (c) Equation with roots [tex]\(\frac{1}{\alpha}\)[/tex] and [tex]\(\frac{1}{\beta}\)[/tex]
To construct the equation with the roots [tex]\(\frac{1}{\alpha}\)[/tex] and [tex]\(\frac{1}{\beta}\)[/tex]:
Change the original equation by substituting [tex]\(x = \frac{1}{t}\)[/tex]:
[tex]\[ 3\left(\frac{1}{x}\right)^2 + 5\left(\frac{1}{x}\right) - 1 = 0 \][/tex]
Multiply through by [tex]\(x^2\)[/tex] to clear the fractions:
[tex]\[ 3 + 5x - x^2 = 0 \][/tex]
Convert to:
[tex]\[ x^2 - 5x - 3 = 0 \][/tex]
#### (d) Equation with roots [tex]\(\alpha + \frac{1}{\beta}\)[/tex] and [tex]\(\beta + \frac{1}{\alpha}\)[/tex]
Roots are [tex]\(\alpha + \frac{1}{\beta}\)[/tex] and [tex]\(\beta + \frac{1}{\alpha}\)[/tex]. These roots are obtained by:
[tex]\[ \left(x - \left(\alpha + \frac{1}{\beta}\right)\right)\left(x - \left(\beta + \frac{1}{\alpha}\right)\right) = 0 \][/tex]
Using the specific values of [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]:
[tex]\[ \left(x - \left(-\frac{5}{6} + \frac{\sqrt{37}}{6} + \frac{6}{1 -\frac{5}{6}} \right)\right) \left(x - \left(-\frac{\sqrt{37}}{6} - \frac{5}{6} \right.+ \frac{6}{1 + \frac{\sqrt{37}}{6} - \frac{5}{6}} \right)\right) = 0 \][/tex]
This simplifies to:
[tex]\[ 3x^2 - 10x + 4 = 0 \][/tex]
#### (e) Equation with roots [tex]\(\frac{\alpha+1}{β+1}\)[/tex] and [tex]\(\frac{\beta+1}{\alpha+1}\)[/tex]
To construct the equation with roots [tex]\(\frac{\alpha+1}{\beta+1}\)[/tex] and [tex]\(\frac{\beta+1}{\alpha+1}\)[/tex]:
[tex]\[ (x - \frac{-5/6 \ + \ \sqrt{37}/6 \ +1 \}{- \ (sqrt(37)\-6)})(X-(5)< \frac(sqrt(37)/6\right) ) = 0 \][/tex]
This simplifies to:
[tex]\[ 9x^2 + 19x + 9 = 0 \][/tex]
### Final compiled results
The equations based on the transformed roots are:
(a) [tex]\(3x^2 + 25x - 25 = 0\)[/tex]
(b) [tex]\(3x + 5\sqrt{x} - 1 = 0\)[/tex]
(c) [tex]\(x^2 - 5x - 3 = 0\)[/tex]
(d) [tex]\(3x^2 - 10x + 4 = 0\)[/tex]
(e) [tex]\(9x^2 + 19x + 9 = 0\)[/tex]
### Step 1: Identify the roots of the given quadratic equation
The roots of the given quadratic equation [tex]\(3x^2 + 5x - 1 = 0\)[/tex] are:
[tex]\[ \alpha = -\frac{5}{6} + \frac{\sqrt{37}}{6}, \quad \beta = -\frac{\sqrt{37}}{6} - \frac{5}{6} \][/tex]
### Step 2: Construct equations for the given conditions
#### (a) Equation with roots [tex]\(5\alpha\)[/tex] and [tex]\(5\beta\)[/tex]
To construct the equation with roots [tex]\(5\alpha\)[/tex] and [tex]\(5\beta\)[/tex], we start by substituting [tex]\(x = 5t\)[/tex] into the original equation to form:
[tex]\[ 3\left(\frac{x}{5}\right)^2 + 5\left(\frac{x}{5}\right) - 1 = 0 \][/tex]
Simplifying, we get:
[tex]\[ \frac{3}{25}x^2 + \frac{5}{5}x - 1 = 0 \][/tex]
[tex]\[ \frac{3}{25}x^2 + x - 1 = 0 \][/tex]
Multiplying through by 25 to clear the fraction gives the final equation:
[tex]\[ 3x^2 + 25x - 25 = 0 \][/tex]
#### (b) Equation with roots [tex]\(\alpha^2\)[/tex] and [tex]\(\beta^2\)[/tex]
To construct the equation with roots [tex]\(\alpha^2\)[/tex] and [tex]\(\beta^2\)[/tex]:
[tex]\[ 3(t^{1/2})^2 + 5t^{1/2} - 1 = 0 \][/tex]
Where [tex]\(t = x^2\)[/tex], this simplifies to:
[tex]\[ 3x + 5\sqrt{x} - 1 = 0 \][/tex]
#### (c) Equation with roots [tex]\(\frac{1}{\alpha}\)[/tex] and [tex]\(\frac{1}{\beta}\)[/tex]
To construct the equation with the roots [tex]\(\frac{1}{\alpha}\)[/tex] and [tex]\(\frac{1}{\beta}\)[/tex]:
Change the original equation by substituting [tex]\(x = \frac{1}{t}\)[/tex]:
[tex]\[ 3\left(\frac{1}{x}\right)^2 + 5\left(\frac{1}{x}\right) - 1 = 0 \][/tex]
Multiply through by [tex]\(x^2\)[/tex] to clear the fractions:
[tex]\[ 3 + 5x - x^2 = 0 \][/tex]
Convert to:
[tex]\[ x^2 - 5x - 3 = 0 \][/tex]
#### (d) Equation with roots [tex]\(\alpha + \frac{1}{\beta}\)[/tex] and [tex]\(\beta + \frac{1}{\alpha}\)[/tex]
Roots are [tex]\(\alpha + \frac{1}{\beta}\)[/tex] and [tex]\(\beta + \frac{1}{\alpha}\)[/tex]. These roots are obtained by:
[tex]\[ \left(x - \left(\alpha + \frac{1}{\beta}\right)\right)\left(x - \left(\beta + \frac{1}{\alpha}\right)\right) = 0 \][/tex]
Using the specific values of [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]:
[tex]\[ \left(x - \left(-\frac{5}{6} + \frac{\sqrt{37}}{6} + \frac{6}{1 -\frac{5}{6}} \right)\right) \left(x - \left(-\frac{\sqrt{37}}{6} - \frac{5}{6} \right.+ \frac{6}{1 + \frac{\sqrt{37}}{6} - \frac{5}{6}} \right)\right) = 0 \][/tex]
This simplifies to:
[tex]\[ 3x^2 - 10x + 4 = 0 \][/tex]
#### (e) Equation with roots [tex]\(\frac{\alpha+1}{β+1}\)[/tex] and [tex]\(\frac{\beta+1}{\alpha+1}\)[/tex]
To construct the equation with roots [tex]\(\frac{\alpha+1}{\beta+1}\)[/tex] and [tex]\(\frac{\beta+1}{\alpha+1}\)[/tex]:
[tex]\[ (x - \frac{-5/6 \ + \ \sqrt{37}/6 \ +1 \}{- \ (sqrt(37)\-6)})(X-(5)< \frac(sqrt(37)/6\right) ) = 0 \][/tex]
This simplifies to:
[tex]\[ 9x^2 + 19x + 9 = 0 \][/tex]
### Final compiled results
The equations based on the transformed roots are:
(a) [tex]\(3x^2 + 25x - 25 = 0\)[/tex]
(b) [tex]\(3x + 5\sqrt{x} - 1 = 0\)[/tex]
(c) [tex]\(x^2 - 5x - 3 = 0\)[/tex]
(d) [tex]\(3x^2 - 10x + 4 = 0\)[/tex]
(e) [tex]\(9x^2 + 19x + 9 = 0\)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.